Centralized Bargaining in Press Wholesale - Frank Christian May; Johannes Münster (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper studies the institutional design of newspaper and periodical wholesale. Motivated by recent developments in Germany, we compare the efficiency properties of two alternative regimes for determining the wholesale margins: collective bargaining (as practised in Germany for the last decades) on the one hand, and local bargaining (as customary in the UK and lately aspired by some German publishers) on the other. We point out several advantages of centralized bargaining: While, in the short run, local bargaining appears more attractive to publishers, it may lead to higher prices for readers and, in the long run, higher total costs of delivery.
Keywords: L82; C78; L41; 330